Indirect Liquid Cooling for Battery Thermal Management: A Review - Ahmadi Syarif Hidayatullah Dardiri; Yaningsih, Indri; Dominicus Danardono Dwi Prija Tjahjana; Muhammad Nizam (International Journal of Integrated Engineering, 2024)
The thermal management system of batteries is a critical aspect of battery management for optimizing battery performance and lifespan. Research has rapidly progressed in battery thermal management in the past decade, mainly by adopting indirect liquid cooling methods. This article provides an in-depth overview of the recent developments in indirect liquid cooling application for battery thermal management, encompassing fundamental principles, types of fluids, and the strengths and weaknesses of this method. Various heat transfer techniques, such as convective heat transfer and heat generation, are also examined to comprehend effective ways of precisely managing battery temperature. The benefits and challenges of this indirect liquid cooling approach are evaluated, considering crucial criteria like safety. The results of this review demonstrate that the indirect liquid cooling method holds promise as an effective solution to address thermal challenges in batteries, with the potential to enhance overall battery performance and durability